PROSEDUR PENGAJUAN SURAT PERINTAH PENCAIRAN DANA (SP2D) UANG PERSEDIAAN MELALUI SISTEM INFORMASI PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPM-PTSP) PROVINSI JAMBI - Purba, Emelia Rita Dameria Br; Putra, Dios Nugraha (Jurusan Akuntansi FEB Universitas Jambi, 2025)
This study aims to examine the procedure for submitting a Fund Disbursement Order (SP2D) for inventory money through the Regional Government Information System of the Republic of Indonesia (SIPD RI) at the Investment and One-Stop Integrated Service Office (DPM-PTSP) of Jambi Province, as well as to identify the obstacles and solutions in its implementation. The research employed a descriptive qualitative method using observation and direct interviews with the expenditure treasurer. The results indicate that the SP2D submission procedure has been integrated with SIPD RI and the Regional General Cash Account (RKUD).